1991
DOI: 10.1111/j.1471-4159.1991.tb08165.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peptides of the Secretin‐Glucagon Family and Cyclic Nucleotides on Tyrosine Hydroxylase Activity in Sympathetic Nerve Endings

Abstract: Previous studies have shown that certain peptides of the secretin-glucagon family stimulate tyrosine hydroxylase activity in sympathetic neurons of the superior cervical ganglion and three of its end organs, i.e., the iris, pineal gland, and submaxillary gland. To determine whether a similar regulation occurs in other sympathetic neurons, the effects of two of these peptides, secretin and vasoactive intestinal peptide, were examined in the right cardiac ventricle of the rat, a tissue innervated primarily by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The stimulatory effect of VIP on cAMP, cGMP, and AA-NAT is potentiated by ␣ 1 -AR agonists (Ho et al, 1987b;Yuwiler, 1987;Chik et al, 1988). However, it has been suggested that, in addition to its postsynaptic effects on pinealocytes, VIP may stimulate TH activity in the sympathetic nerve endings (Schwarzschild and Zigmond, 1991). A study comparing the effects of VIP and ISO on the same culture of rat pinealocytes has shown that VIP is very effective in stimulating MEL synthesis (EC 50 ϭ 0.11 nM), but that at optimal doses (1 to 10 nM) its effect is approximately 2 to 3 times lower than that induced by optimal doses (1 to 10 M) of a ␤ 1 -AR agonist .…”
mentioning
confidence: 98%
“…The stimulatory effect of VIP on cAMP, cGMP, and AA-NAT is potentiated by ␣ 1 -AR agonists (Ho et al, 1987b;Yuwiler, 1987;Chik et al, 1988). However, it has been suggested that, in addition to its postsynaptic effects on pinealocytes, VIP may stimulate TH activity in the sympathetic nerve endings (Schwarzschild and Zigmond, 1991). A study comparing the effects of VIP and ISO on the same culture of rat pinealocytes has shown that VIP is very effective in stimulating MEL synthesis (EC 50 ϭ 0.11 nM), but that at optimal doses (1 to 10 nM) its effect is approximately 2 to 3 times lower than that induced by optimal doses (1 to 10 M) of a ␤ 1 -AR agonist .…”
mentioning
confidence: 98%
“…Subsequently, STAT proteins translocate to the nucleus and bind to conserved genomic regulatory sequences to rapidly activate gene transcription [42], [43]. The cytokines also activate components of other intracellular signaling pathways, including Ras, mitogen-activated protein kinase (MAPK), and the Fos-Jun (AP-1) transcription factors [44][46], and activate direct interaction between STAT1 and AP-1 [47]. This supports our AP-1 motif detected by rGADEM in the STAT1 enriched regions.…”
Section: Resultsmentioning
confidence: 99%
“…It lowers the production of cGMP levels in a wide range of tissues, with negligible effect on cAMP levels (Mulsch et al 1988). 8-Bromoguanosine 3 0 ,5 0 -cyclic monophosphate sodium salt monohydrate (8-Br-cGMP) is a cell permeable nonhydrolyzable derivative of cGMP (Schwarzschild and Zigmond 1991). Staurosporine is a potent, cell permeable, broad spectrum inhibitor of protein kinases (Rüegg and Burgess 1989).…”
Section: Chemicalsmentioning
confidence: 99%